2013
DOI: 10.1038/bjc.2013.148
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of circulating miR-18a in plasma of patients with oesophageal squamous cell carcinoma

Abstract: Background:Several recent studies demonstrated that microRNAs are stably detectable in plasma/serum. We tested whether miR-18a, which is located in the miR-17-92 cluster and reported to be highly expressed in tissues of oesophageal squamous cell carcinoma (ESCC), served as a plasma biomarker in patients with ESCC.Methods:This study was divided into three steps: (1) confirmation of higher miR-18a levels in primary ESCC tissues and cell lines than normal ESCC tissues and a human fibroblast cell line. (2) Evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 47 publications
5
76
0
3
Order By: Relevance
“…Splitting miRNA expression levels by the sample median was the choice of preference in three studies evaluated in the present analyses with Forest plots [13 -15]. Other studies defi ned the cut-offs using Youden index (N ϭ 1) [12] or normal tissue (N ϭ 2) [16,17]. One study did not defi ne the cut-off [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Splitting miRNA expression levels by the sample median was the choice of preference in three studies evaluated in the present analyses with Forest plots [13 -15]. Other studies defi ned the cut-offs using Youden index (N ϭ 1) [12] or normal tissue (N ϭ 2) [16,17]. One study did not defi ne the cut-off [18].…”
Section: Discussionmentioning
confidence: 99%
“…HRs and 95% CIs directly [13] or described logrank tests including number of events in which it was possible to calculate the corresponding HRs and their 95% CIs [12,14,15]. Three studies reported no statistical signifi cant association between miR-21 expression levels in cancerous tissue and survival [12 -14] whereas only one study showed a signifi cant and inverse correlation between miR-21 and OS [15].…”
Section: Mir-21 and Mir-375 As Prognostic Markers In Escc And Eac (Comentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, circulating miR-18a has been demonstrated to be a promising biomarker for the diagnosis and monitoring of esophageal squamous cell carcinoma (35).…”
Section: Discussionmentioning
confidence: 99%
“…With the capacity to target hundreds of genes, they play an important role in a variety of biological processes, such as cell differentiation, proliferation, and apoptosis, and it is not surprising that many studies have now identified an association between dysregulation of miRNAs and carcinogenesis, including that of HNC (Miska, 2005;Du and Zamore, 2007;Avissar et al, 2009;Keutgen et al, 2012;Gombos et al, 2013;Hirajima et al, 2013). miRNAs are also expressed stably in plasma, serum, and other body fluids, indicating their potential use as clinical biomarkers.…”
Section: Introductionmentioning
confidence: 99%